Trânsitos na prostituição: entre lugares, conexões e expectativas - Silva, Lívia Freire da (2020)
This ethnography was constructed to understand the representations, cultural dynamics, transits between states, the possible comings, and goings of prostitutes in the sex market. For this, I analyze the transits that constitute female prostitution within a circuit that comprises Paraíba and Rio Grande do Norte, taking as the central point of this study the prostitution as an agency that constitutes individual choices and projects. The clipping of ethnographic area comprises spaces that border federal and state highways, where women build specific transit routes and a mutual support network. In this respect, transits are organized by them and so that this displacement is possible they essentially travel by hitchhiking and with previous directions or contacts from the cabarets to which they travel. In this context I have identified categories that demarcate how prostitution develops in each city studied, indicating that entering the activity is a choice that women make in the face of their possibilities: economic, family and access to education. I understand prostitution as an economic activity that exchanges sex and money. In this sense, it presents itself as an activity where the woman constantly deals with the body and sexuality and exercises sexuality beyond the domestic sphere. Through this bias it is possible to notice how prostitutes deal with their bodies to meet economic needs. Understanding this factor is what will provide a basis for thinking about prostitution beyond the lack of economic opportunity.